Paradigma Revolusi Sains Dalam Perkembangan Ilmu Pengetahuan - Muhammad Wahidin Annaba; Alvira Syahila; Nayla Sahla; Rabial Razki Ramadhan; Bima Prima Panggayuh (Yayasan Al-Afif, 2026)
Scientific development has become an important issue in the philosophy of science because knowledge continues to evolve alongside changes in perspectives, methods, and scientific frameworks. This study aims to analyze the paradigm of scientific revolution in the development of knowledge through thomas s. Kuhn’s perspective and to explain how paradigm shifts influence scientific progress. The study was conducted to address the understanding that scientific advancement is not merely a cumulative process but also involves structural changes in scientific thinking and practice. This research employed a qualitative approach using a library research design. Data were collected through documentation techniques from scientific journals and academic literature relevant to the topic and were analyzed using descriptive-interpretative content analysis. The findings show that the development of knowledge occurs through stages consisting of normal science, anomaly, scientific crisis, scientific revolution, and the establishment of a new paradigm. The study also found that changes in scientific paradigms are influenced by both internal scientific dynamics and external factors such as social transformation and Technological advancement. These findings indicate that thomas s. Kuhn’s theory of scientific revolution remains relevant as an analytical framework for understanding the dynamics of contemporary knowledge development and provides conceptual implications for future academic studies and scientific practice.